Cocktailed fragment screening by X-ray crystallography of the antibacterial target undecaprenyl pyrophosphate synthase from Acinetobacter baumannii - Thorpe, James H. (International Union of Crystallography, 2020)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Direct soaking of protein crystals with small-molecule fragments grouped into complementary clusters is a useful technique when assessing the potential of a new crystal system to support structure-guided drug discovery. It provides a robustness check prior to any extensive crystal screening, a double check for assay binding cutoffs and structural data for binding pockets that may or may not be picked out in assay measurements. The structural output from this technique for three novel fragment molecules identified to bind to the antibacterial target Acinetobacter baumannii undecaprenyl pyrophosphate synthase are reported, and the different physicochemical requirements of a successful antibiotic are compared with traditional medicines.